Aesthetic experience in comics: image, visual culture and experience (Revista Apotheke, 2025)
Establishing a dialogue between comic books and the academic space of visual arts implies exploring aspects of contemporary visual culture, its context, and the artistic and aesthetic interpretations of the object. Thus, this article analyzes comic books as a means capable of providing aesthetic experiences and expanding their poetic, narrative, and symbolic potentialities as an alternative to understanding current artistic productions. Therefore, bibliographical research was carried out on the concept of experience by John Dewey, establishing interpolations with the image and visual culture, seeking to understand the possible spaces of dialogue between comic books and visual arts, and teaching.
Keywords: John Dewey; Visual Arts; Comic Book; Experience; Visual Culture